2016
DOI: 10.1002/jmri.25243
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of left ventricular volume and function in middle‐aged healthy chinese people with 3 Tesla MRI

Abstract: The left ventricular volume and function differs in women compared with men in the middle-aged population, and these parameters have a tendency of decrease with ageing. J. Magn. Reson. Imaging 2016;44:1143-1150.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 30 publications
2
21
2
Order By: Relevance
“…However, in the recently reported Singapore Chinese study, LVEF and RVEF were lower in both sexes as compared with our study and the other studies mentioned above, which were not accounted for by different tracing methods because they used similar methods to the studies by Maceira et al and Hudsmith et al The possible mechanisms for these differences are not known. Li et al provided values for the LV in 90 middle‐aged healthy Chinese subjects in which LVEDVi, LVESVi, and LV mass index were also smaller than the values recorded in our study. This difference could be explained by a different tracing method and narrow age population included in their study.…”
Section: Discussioncontrasting
confidence: 82%
See 4 more Smart Citations
“…However, in the recently reported Singapore Chinese study, LVEF and RVEF were lower in both sexes as compared with our study and the other studies mentioned above, which were not accounted for by different tracing methods because they used similar methods to the studies by Maceira et al and Hudsmith et al The possible mechanisms for these differences are not known. Li et al provided values for the LV in 90 middle‐aged healthy Chinese subjects in which LVEDVi, LVESVi, and LV mass index were also smaller than the values recorded in our study. This difference could be explained by a different tracing method and narrow age population included in their study.…”
Section: Discussioncontrasting
confidence: 82%
“…Differences between the sexes with regard to ventricular parameters has been reported in several studies . Two studies showed no differences between the sexes in LVEDVi, LVESVi, and LVEF after adjustment for BSA . Usually, LV and RV volumes are larger in males than in females, even after adjustment for BSA.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations